Climate-smart agriculture measurement, reporting and verification in the Republic of Zambia. Annexes - World Agroforestry Centre; Unique Forestry and Land Use (2019)
Annexes for the Climate-smart agriculture measurement, reporting and verification in the Republic of Zambia report.